Hofstede’s cultural dimensions and public communication in Morocco: between identity heritage and institutional modernity - Arbaoui Faiçal (International Journal of Scientific Research and Innovative Studies, 2025)
Globalisation and digitalisation have had a profound impact on public discourse and modern communication within contemporary institutions. In Morocco, these developments have resulted in an ongoing attempt to reconcile the tensions inherited from deeply rooted cultures with the contemporary demands of institutionalisation, namely efficiency and transparency. Based on Hofstede's intercultural model and the work of Bourdieu, Giddens, Morin, and Habermas, this article takes a systemic approach to culture and communicational interactions in public organisations in Morocco. Drawing on an analysis of national administrative culture and theories of structuration and communicational rationality, the author shows the impact of societal values, hierarchical distance, collectivism, and cohesion on inter-state relations and public institutions. Far from being reduced to the circulation of information, public communication, in its modern function, is articulated around a field of tension and power relations where modernity, tradition, and the space for co-civism are negotiated. Keywords : Hofstede's cultural dimensions and public communication in Morocco: between identity heritage and institutional modernity. Received Date: August 21, 2025 Accepted Date: September 13, 2025 Published Date: October 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/477